Strategies for provisioning and operating VHE services in multi-access networks. - Daoud, F. (IEEE Communications magazine)
Providing advanced services over multi-access networks is a challenging issue for service providers as well as for network operators. This article presents a framework for provisioning virtual home environment services dealing with these issues. We evaluate ongoing standardization activities in this area, and propose strategies suitable for deployment, and operating associated systems and services